2016
DOI: 10.1007/s12275-016-5562-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutational inactivation of OprD in carbapenem-resistant Pseudomonas aeruginosa isolates from Korean hospitals

Abstract: In our previous study, the first structural gene (GGTI) encoding g-glutamyl transpeptidase was cloned and characterized from the fission yeast Schizosaccharomyces pombe, and its transcription, using the GGTI-lacZ fusion gene, containing the 1,085 bp upstream region from the translational initiation point, was found to be enhanced by sodium nitroprusside and L-buthionine-(S,R)-sulfoximine (BSO). In the present work, regulation of the GGTI gene was further elucidated. Non-fermentable carbon sources, such as acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 21 publications
8
31
0
Order By: Relevance
“…In the study of Yi et al, 2006 [40], imipenem resistance is mainly mediated by OprD deficiency. In agreement with that, Kim and coauthors have recently reported that OprD inactivation is the most common mechanism of carbapenem resistance in P. aeruginosa isolated from Korean patients [42].…”
Section: Pfge Clone Number Of Isolates Carbapenemase Genesupporting
confidence: 85%
“…In the study of Yi et al, 2006 [40], imipenem resistance is mainly mediated by OprD deficiency. In agreement with that, Kim and coauthors have recently reported that OprD inactivation is the most common mechanism of carbapenem resistance in P. aeruginosa isolated from Korean patients [42].…”
Section: Pfge Clone Number Of Isolates Carbapenemase Genesupporting
confidence: 85%
“…On the other hand, the literature does not associate the PmrA and NalC amino acid changes observed here to resistant strains [25,26]. In addition, the 20 oprD mutations identified for all strains may be a feature of ST277, as specific amino acid substitutions in OprD have been potentially associated to MLST profiles [24].…”
Section: Discussionmentioning
confidence: 58%
“…We analyzed mutational events in some genes that can contribute to enhance the bacterial resistance phenotype. Among these genetic alterations, those already described as related to increased resistance are: activator deletion of mexT that leads to low sensitivity to chlorophenylcholine and fluoroquinolones [20]; mexZ nucleotide deletion associated to aminoglycoside, cefepime, tetracyclines and macrolides resistance [8,21]; mutation in PhoQ linked to colistin-resistant phenotype [22]; GyrA alterations creating quinolone-resistant strains [23]; and oprD frameshift related to imipenem resistance [8,24]. On the other hand, the literature does not associate the PmrA and NalC amino acid changes observed here to resistant strains [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Only two mutations are nonsynonymous, but they are unable to affect the flow of molecules through this bacterial membrane' pore. The presence of a potential association has been suggested between specific amino acid substitutions in OprD and MLST profiles [26] . Perhaps the mutations observed here can be characteristic of ST277.…”
Section: Mutations In the Pmrab Or Phopq Two-component Regulatory Sysmentioning
confidence: 99%